Constructing Bridges of Support: School Counsellors’ Experiences of Student Suicide - Christianson, Carley L.; Everall, Robin D. (Canadian Journal of Counselling and Psychotherapy, 2008)
School counsellors are professionals with specialized training in personal counselling who work in school settings. They are usually the front-line school personnel required to deal with youth suicide. Despite the important roles of school counsellors, there is little research that explores the experiences of school counsellors who have lost clients to suicide. In this study, seven school counsellors were individually interviewed, and data were analyzed using a basic interpretative qualitative method informed by grounded theory. Themes related to training and practice standards, support resources, and self-care were identified by participants as critical to personal well-being and continued effective professional functioning. Personal and professional implications are discussed.